Necessary Condition Analysis on the Relationship between Fear of Missing Out, Social Networking Addiction, and Psychological Well-Being - Ravi Shanker Datti; Maneela Sirisety; Mohana Rupa Nekkanti; Nalini Bikkina; Eduard V. Patrakov; Lioudmila Baturina (European Journal of Mental Health)
Introduction: With the growth of technology and increasing accessibility to various platforms, concerns surrounding the impact of technology on individuals’ well-being are also on the rise. Researchers are making significant efforts to understand this constantly evolving phenomenon. Aims: The current study aims to investigate the interrelationships between fear of missing out (FoMO), social networking addiction (SNA), and psychological well-being (PWB), as well as the relation between SNA scores and sociodemographic variables. Methods: This study employs a recently developed data analysis approach called Necessary Condition Analysis (NCA) to observe essential conditions within SNA, PWB, and FoMO. The study’s main objective is to determine whether low/high levels of FoMO and SNA correspond to high/low levels of PWB. To address this objective, a convenience sample of 449 participants aged 17–40 years was selected. Statistical analyses were conducted using the NCA package to investigate the relationships between these variables. A chi-square test was also performed to assess the associations between sociodemographic variables and probable SNA cases based on the established cut-off scores. Results: The results indicated that high levels of FoMO are necessary for high levels of SNA (Effect Size (d) = .15 and p < .001), and high levels of PWB were found to be necessary for low levels of FoMO (d = .23 and p < .001) and SNA (d = .16 and p = .01) and vice versa. It was also observed associations between the demographic variables of gender, marital status, and residence, and SNA. Conclusions: This research contributes to the current discussions concerning the influence of social media on personal well-being and the field of media psychology. The findings obtained can help in guiding the development of interventions and strategies aimed at promoting psychological welfare within digitally interconnected communities.